Crisis del multiculturalismo en América Latina Conflictividad social y respuestas críticas desde el pensamiento político indígena - Zapata Silva, Claudia (Afrontar las crisis desde América Latina, 2019)
Has the quality of life of indigenous peoples in Latin America improved after three decades in which legislation has been built that recognizes them? Statistical information and the increase in social conflict in indigenous territories leads to a negative answer to this question. This essay is a critical reflection on the exhaustion of the multicultural moment in Latin America from the dialogue with the critical thinking that has emerged from the movements themselves, especially from activists and intellectuals who denounce the relationship between recognition policies and extractivist capitalism, resisting the colonialist images that these policies reproduce because they deny the historicity and political potential of their peoples.